2018
DOI: 10.1038/s41598-018-21692-4
|View full text |Cite
|
Sign up to set email alerts
|

Biomining of MoS2 with Peptide-based Smart Biomaterials

Abstract: Biomining of valuable metals using a target specific approach promises increased purification yields and decreased cost. Target specificity can be implemented with proteins/peptides, the biological molecules, responsible from various structural and functional pathways in living organisms by virtue of their specific recognition abilities towards both organic and inorganic materials. Phage display libraries are used to identify peptide biomolecules capable of specifically recognizing and binding organic/inorgani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 38 publications
1
25
0
Order By: Relevance
“…[4][5][6][7][8][9][10] Several studies on the adsorption of peptide molecules on the MoS 2 surface have been reported and indicate that the hydrophobicity, aromatic structure and electrostatic properties of amino acids are important factors affecting adsorption and surface assembly. [87][88][89][90][91][92] However, experimental data remain qualitative in nature, including AFM, TEM imaging, binding information from concentration measurements, QCM, XPS, CD, Raman shis, and relative ranking from washing cycles in phage display. Quantitative binding energies and conformations in solutions are not accessible.…”
Section: Peptide Recognition On Mos 2 Surfaces and Identication Of Bmentioning
confidence: 99%
See 2 more Smart Citations
“…[4][5][6][7][8][9][10] Several studies on the adsorption of peptide molecules on the MoS 2 surface have been reported and indicate that the hydrophobicity, aromatic structure and electrostatic properties of amino acids are important factors affecting adsorption and surface assembly. [87][88][89][90][91][92] However, experimental data remain qualitative in nature, including AFM, TEM imaging, binding information from concentration measurements, QCM, XPS, CD, Raman shis, and relative ranking from washing cycles in phage display. Quantitative binding energies and conformations in solutions are not accessible.…”
Section: Peptide Recognition On Mos 2 Surfaces and Identication Of Bmentioning
confidence: 99%
“…Other reported peptides with high binding constants in experiments include GVIHRNDQWTAPGGG and DRWVARDPASIFGGG, as well as a weakly binding/non-binding peptide SVMNTSTKDAIEGGG. 88 The interpretation of binding residues in ref. 88 relied exclusively on MD simulation with a misleading force eld, indicating Val, Pro, and Trp as binding residues, whereas Val and Pro are expected to bind weakly according to other studies.…”
Section: Peptide Recognition On Mos 2 Surfaces and Identication Of Bmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown that the presence of the phenyl ring in peptide sequences with and without F is sufficient as a molecular switch to convert cuboctahedral or cubic nanocrystals into tetrahedral during the growth process [86]. In particular, decorated metal nanoparticles have applications in biomining [87], cell targeting, imaging, and therapeutic purposes [88,89]. Specific binding of peptides on graphene [90,91,92,93,94] has also been investigated both computationally and experimentally.…”
Section: Organic–inorganic Interface Simulations For Smart Novel Mmentioning
confidence: 99%
“…Particulate matter binding peptides (binding of Cu and Zn compounds) were used as probes to detect air pollution (Alvin, Tanaka, & Okochi, ). Material binding peptides were also adapted for biomining, whereby magnetic nanoparticles were coated with a molybdenite (MoS 2 ) binding peptide to harvest the trace element in copper and tungsten mines (Cetinel, Aminpour, Wang, Borujeny, Sharma, & Montemagno, ).…”
Section: Introductionmentioning
confidence: 99%